2018
DOI: 10.1111/1751-7915.13340
|View full text |Cite
|
Sign up to set email alerts
|

Engineered cell‐to‐cell signalling within growing bacterial cellulose pellicles

Abstract: Summary Bacterial cellulose is a strong and flexible biomaterial produced at high yields by Acetobacter species and has applications in health care, biotechnology and electronics. Naturally, bacterial cellulose grows as a large unstructured polymer network around the bacteria that produce it, and tools to enable these bacteria to respond to different locations are required to grow more complex structured materials. Here, we introduce engineered cell‐to‐cell communication into a bacterial cellulose‐producing st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 25 publications
(35 reference statements)
0
33
0
2
Order By: Relevance
“…These studies together give a comprehensive guide for the construction of vectors of a high potential to be effective in the numerous species from this genus. These recent achievements include the use of quorum sensing (QS) synthetic biology elements known to be functional in E. coli (Florea et al 2016;Walker et al 2018). The first example of employment of these elements was the application of inducible lux promoter and luxR gene for modification of K. rhaeticus strain (Florea et al 2016).…”
Section: Molecular and Synthetic Biology Tools For Targeted Strain Mamentioning
confidence: 99%
See 1 more Smart Citation
“…These studies together give a comprehensive guide for the construction of vectors of a high potential to be effective in the numerous species from this genus. These recent achievements include the use of quorum sensing (QS) synthetic biology elements known to be functional in E. coli (Florea et al 2016;Walker et al 2018). The first example of employment of these elements was the application of inducible lux promoter and luxR gene for modification of K. rhaeticus strain (Florea et al 2016).…”
Section: Molecular and Synthetic Biology Tools For Targeted Strain Mamentioning
confidence: 99%
“…This study showed that the capability of cellulose production was lowered and eventually switched off with increasing concentration of N-acyl homoserine lactone (AHL) in the media. Another study reported the construction of Sender and Receiver recombinant K. rhaeticus strains (Walker et al 2018). The first strain produced AHL in response to an environmental signal, while the second strain induced recombinant protein expression (red fluorescent protein, RFP) in response to AHL in a concentration-dependent manner.…”
Section: Molecular and Synthetic Biology Tools For Targeted Strain Mamentioning
confidence: 99%
“…A follow-up paper from the same team later showed that induction of gene expression from plasmids in these cells could be directed by the presence of other engineered cells grown in co-culture [45]. Strains engineered in Florea et al (2016) to respond to the AHL inducer and produce red fluorescent protein (RFP) were partnered with new strains engineered to constitutively express an enzyme (LuxI) that synthesizes AHL [46].…”
Section: Synthetic Biology Toolkits For Bringing New Functionality Tomentioning
confidence: 99%
“…These new strains (known as 'sender' cells) secrete AHL molecules into the media and when they are at high concentration and close proximity to the AHL-controlled cells ('receiver cells') they trigger them to produce RFP. The authors showed that these two cells could be co-cultured to grow BC pellicles that trigger their own red fluorescence and more importantly could be used to grow materials that self-sense the boundaries engineered cell populations and trigger gene expression only at these sites [45]. This foundational advance holds future promise for growing BC-based materials with genetically-encoded self-patterning.…”
Section: Synthetic Biology Toolkits For Bringing New Functionality Tomentioning
confidence: 99%
“…Florea et al genetically engineered a BC-producing strain so that cellulose production and red fluorescent protein (RFP) production could be controlled by the addition of a small molecule inducer, which allowed for spatial patterning of the cellulose pellicle ( 35 ). Walker et al genetically engineered “sender” and “receiver” strains of a BC-producing bacteria to achieve boundary detection in a fused pellicle ( 36 ). Even with encouraging early efforts in this area, the potential functionality of smart ELMs composed of BC is limited by our ability to engineer BC-producing bacteria to secrete recombinant proteins and sense specific external cues.…”
Section: Introductionmentioning
confidence: 99%